DEVELOPMENT OF THE INQUIRY-BASED WORKSHEET IN PLANT NUTRITION CONCEPTS OF VIII-TH GRADE IN JUNIOR HIGH SCHOOL - SITI MUAMMAROH (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
There were no inquiry-based student worksheet of plant nutrition concept in VIIIth grade in Junior High School PGRI 29 Surabaya. Therefore, the aim of this research was 1) to develope the inquiry-based student worksheet, 2) to describe the validity of student-worksheet, 3) to describe the empirical validity based on student responses. The research design during the development used was 4-D model without the dessiminate phase. Based on the data showed that the developed student workesheet were 1) valid to be used by the score of 89% in the very valid category, 2) student responses in the score of 89,53% (very good category). Key words: Development of inquiry-based student worksheet; nutrients in plant